PENGARUH KEMAMPUAN TEKNIK PEMAKAI DAN EFEKTIVITAS SISTEM INFORMASI AKUNTANSI (SIA) TERHADAP KINERJA INDIVIDUAL - Jayantara, I Ketut; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
This study aims to determine the effect of mechanical user capabilities and effectiveness of accounting information systems (AIS) on the individual performance in village credit institutions in Mengwi. Samples in this study were 154 respondents to the sampling technique used was purposive sampling. Data collection methods used were a questionnaire method. Data analysis technique used is the technique of multiple linear regression analysis. According to the research by distributing questionnaires to 154 respondents, it can be drawn the conclusion that the wearer engineering capabilities and effectiveness of the accounting information system and significant positive effect on the performance of the individual. This means increasing the wearer engineering capabilities and effectiveness of the SIA then there is also an increase in the performance of individual on Credit Institutions Village in Mengwi.
Keywords: Ability Engineering User, Effectiveness of Accounting Information Systems (AIS), Individual Performance